Polyimide film having excellent filler dispersibility and display device including the same
A polyimide film with uniformly dispersed fillers in a specific density ratio and concentration range addresses dispersibility issues, enhancing mechanical and optical properties for use as display device cover windows.
Patent Information
- Application Number
- JP2023500353
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-09
- Filing Date
- 2021-07-09
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-07-09
AI Technical Summary
Existing polyimide films used as cover windows in display devices face challenges in uniformly dispersing fillers, leading to issues with mechanical and optical properties such as increased haze, reduced tensile strength, and decreased flexibility.
A polyimide-based matrix with uniformly dispersed fillers, characterized by a true density ratio (DR) of 1.10 or less and a particle volume concentration (PVC) of 5 to 38%, using silica particles surface-treated with an organic compound, ensures excellent filler dispersibility and mechanical properties.
The polyimide film achieves improved mechanical properties like Young's modulus of 5.0 GPa or more, elongation rate of 15% or more, press-fit hardness of 45 or more, and optical properties with light transmittance of 85% or more and haze of 1% or less, effectively protecting display devices.
Smart Images

Figure 0007617241000011 
Figure 0007617241000012 
Figure 0007617241000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide film having excellent filler dispersibility and a display device including the same. [Background technology]
[0002] Polyimide (PI) resins are excellent in terms of insolubility, chemical resistance, heat resistance, radiation resistance, and low-temperature properties, and are used as automotive materials, aviation materials, spacecraft materials, insulating coating agents, insulating films, protective films, etc.
[0003] In recent years, as display devices have become thinner, lighter, and more flexible, the use of polyimide films instead of glass as cover windows for display devices has been considered. In order to use a polyimide film as a cover window for a display device, the polyimide film must have excellent mechanical properties such as hardness, abrasion resistance, and flexibility, and excellent optical properties such as visibility and light transmittance. In order to impart desired physical properties, a filler may be added to the polyimide film. Summary of the Invention [Problem to be solved by the invention]
[0004] An object of one embodiment of the present invention is to provide a polyimide film in which a filler is uniformly dispersed in a polyimide resin.
[0005] An object of one embodiment of the present invention is to provide a polyimide film having a true density ratio (DR) to density gradient tube density of 1.10 or less.
[0006] An object of one embodiment of the present invention is to provide a polyimide film having a particle volume concentration (PVC) of 5 to 38%. [Means for solving the problem]
[0007] One embodiment of the present invention provides a polyimide film comprising a polyimide matrix and a filler dispersed in the polyimide matrix, the polyimide film having a true density ratio (DR) to density gradient tube density of 1.10 or less.
[0008] The true density ratio (DR) to the density gradient tube density is calculated by the following formula 1.
[0009] <Expression 1> Density Ratio(DR)=true density / density gradient tube density
[0010] The polyimide-based film can have a particle volume concentration (PVC) of 5 to 38%.
[0011] The particle volume concentration (PVC) is calculated by the following formula 2.
[0012] <Expression 2> PVC(%)=[V1 / (V1+V2)]*100
[0013] In Equation 2, V1 is the volume of the filler and V2 is the volume of the matrix.
[0014] The filler can include silica (SiO2).
[0015] At least a portion of the silica (SiO2) can be surface-treated with an organic compound having an alkoxy group.
[0016] The filler may have an average particle size of 5 to 50 nm.
[0017] The content of the filler may be 5 to 50% by weight based on the total weight of the polyimide film.
[0018] The polyimide film may have a Young's modulus of 5.0 GPa or more.
[0019] The polyimide film may have an elongation of 15% or more.
[0020] The polyimide film may have an indentation hardness of 45 or more.
[0021] The polyimide-based film may have a yellowness index of 3 or less.
[0022] The polyimide film may have a haze of 1% or less.
[0023] The polyimide film may have a light transmittance of 85% or more.
[0024] Another embodiment of the present invention provides a display device that includes a display panel and a polyimide-based film disposed on the display panel. Effect of the Invention
[0025] According to an embodiment of the present invention, a polyimide film having excellent filler dispersion can be produced.
[0026] Generally, when a filler is dispersed in a polyimide film, the haze of the polyimide film may decrease, but according to one embodiment of the present invention, the polyimide film has excellent filler dispersion and a true density ratio (DR) to the density in a density gradient tube of 1.10 or less. As a result, the polyimide film of the present invention has excellent optical properties and excellent mechanical properties.
[0027] The polyimide-based film according to an embodiment of the present invention has excellent optical and mechanical properties, and when used as a cover window of a display device, it can effectively protect the display surface of the display device. [Brief description of the drawings]
[0028] [Figure 1]1 is a schematic diagram of a polyimide-based film according to an embodiment of the present invention. [Diagram 2] This shows the difference in pores inside a film depending on the true density ratio (DR) of the film to the density gradient tube density. [Diagram 3] This shows the difference in voids inside the film depending on the particle volume concentration (PVC) of the film. [Figure 4] FIG. 2 is a schematic diagram illustrating a dispersion state of a filler in a polyimide film according to an embodiment of the present invention. [Diagram 5] 11 is a cross-sectional view of a portion of a display device according to another embodiment of the present invention. [Figure 6] FIG. 6 is an enlarged cross-sectional view of part “P” in FIG. 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the embodiments described below are presented for the purpose of illustration to help a clear understanding of the present invention, and are not intended to limit the scope of the present invention.
[0030] The shapes, sizes, ratios, angles, numbers, and the like disclosed in the drawings to explain the embodiments of the present invention are merely illustrative, and the present invention is not limited to the matters shown in the drawings. Throughout the specification, the same components may be referred to by the same reference numerals. In the description of the present invention, if it is determined that a detailed description of related known art may unnecessarily obscure the gist of the present invention, the detailed description will be omitted.
[0031] When the terms "including," "having," "made," etc. are used in this specification, other parts may be added unless the expression "only" is used. When an element is expressed in the singular, it includes the plural unless otherwise expressly stated. In addition, when analyzing an element, it is interpreted as including a margin of error even if there is no separate express description.
[0032] When describing a positional relationship between two parts, for example "on", "at the top", "below", "to the side", etc., one or more other parts may be located between the two parts, unless the words "immediately" or "directly" are used.
[0033] Spatially relative terms such as "below," "beneath," "lower," "above," "upper," and the like may be used to easily describe the relationship of one element or component to another element or component as shown in the figures. Spatially relative terms should be understood as terms that include different orientations of elements in use or operation in addition to the orientation shown in the figures. For example, if an element shown in the figures is turned over, an element described as "below" or "beneath" another element may be placed "above" the other element. Thus, the exemplary term "below" can include either an orientation of below or above. Similarly, the exemplary term "upper" can include either an orientation of above or below.
[0034] In explaining temporal relationships, for example, when the temporal precedence is explained using terms such as "after," "following," "next to," or "before," it is possible to include cases where things are not consecutive, since the expressions "immediately" or "directly" are not used.
[0035] Although the terms "first", "second" and the like are used to describe various components, these components are not limited by the terms. The terms are used merely to distinguish one component from another. Therefore, the first component referred to below may be the second component within the technical concept of the present invention.
[0036] The term "at least one" should be understood to include all possible combinations of one or more of the associated items. For example, "at least one of the first, second, and third items" can mean not only the first, second, or third item, respectively, but also any possible combination of items from two or more of the first, second, and third items.
[0037] The respective features of the various embodiments of the present invention may be partially or fully combined or combined with each other, and various interlocking and driving techniques may be possible, and each embodiment may be implemented independently of each other or may be implemented together in association with each other.
[0038] FIG. 1 is a schematic diagram of a polyimide-based film 100 according to one embodiment of the present invention.
[0039] As shown in FIG. 1, a polyimide-based film 100 according to an embodiment of the present invention includes a polyimide-based matrix 110 and a filler 120 dispersed in the polyimide-based matrix.
[0040] In the polyimide-based film 100 according to an embodiment of the present invention, the true density ratio (DR) of the film 100 to the density gradient tube density is 1.10 or less.
[0041] The true density ratio (DR) of the film 100 to the density gradient tube density is calculated by the following formula 1.
[0042] <Expression 1> Density Ratio(DR)=true density / density gradient tube density
[0043] True density means solid density, and refers to the density of only the part completely filled with material, excluding voids between particles. According to one embodiment of the present invention, true density is the density of only the part filled with polyimide matrix 110 and filler 120, excluding voids.
[0044] The true density may vary depending on the size of the sample of the film 100 being measured. Therefore, according to one embodiment of the present invention, the true density of the film 100 may be determined by powder analysis.
[0045] Specifically, a sample of film 100 (10 × 10 cm 2 ) 1×1cm 2 The sample is cut into small pieces of the following size and placed in a sample holder together with iron balls (crushed material). A cryo-crusher (Japan Analytical Industry, JFC-300) is filled with more than 2 / 3 of liquid nitrogen, and the sample holder containing the cut sample is connected to the cryo-crusher, and the chamber is closed. The sample is crushed using the cryo-crusher at a pre-cool rate of 15 minutes / run time of 15 minutes or more. The true density of the crushed film 100 sample is measured seven times using a Micromeritics AccuPyc1340 Pycnometer device (using helium gas). The highest and lowest true density values of the measured film 100 are excluded, and the average of the remaining true density values is the true density of the film 100 in the present invention.
[0046] Density gradient tube density refers to the density measured using a density gradient tube. A density gradient tube is one method for measuring density.
[0047] According to one embodiment of the present invention, the density gradient tube of film 100 can be determined using a density gradient tube according to standard ASTM D1505.
[0048] Specifically, a density gradient tube is a glass cylinder in which a liquid with a high specific gravity is placed at the bottom and a liquid with a low specific gravity is placed at the top, creating a density gradient between them, and when a film 100 sample piece is placed in such a density gradient tube, it hangs and stops at the same position as the density, and the density gradient at that position allows the density gradient tube density of the film 100 sample to be known. The density gradient of a density gradient tube can be known by inserting a glass spherical float with a known specific gravity, by measuring the specific gravities of zinc chloride aqueous solutions of various concentrations in advance and then fixing them in the density gradient tube, or by a colorimetric method using a dye that dissolves only in one of the liquids with different specific gravities in the density gradient tube.
[0049] The true density ratio (DR) of film 100 to the density gradient tube density will be described in detail below with reference to Fig. 2. Fig. 2 shows the difference in voids within film 100 depending on the true density ratio (DR) of film 100 to the density gradient tube density.
[0050] The true density ratio (DR) of film 100 to density gradient tube density indicates the degree of voids (porosity) present in film 100 using the ratio of density gradient tube density to true density of film 100. True density is the density of matrix 110 and filler 120 excluding voids from film 100, and density gradient tube density is the density of film 100 including voids, and the porosity of film 100 can be expressed through the ratio of true density to density gradient tube density.
[0051] As shown in FIG. 2, as the true density ratio (DR) of film 100 to the density gradient tube density increases, the voids in film 100 increase, and conversely, as the true density ratio (DR) to the density gradient tube density decreases, the voids in film 100 decrease.
[0052] In general, when the film 100 includes the filler 120, voids in the film 100 may occur depending on the degree of dispersion of the filler 120. If the filler 120 is poorly dispersed and aggregates, the spaces between the fillers may not be sufficiently filled by the matrix 110, resulting in voids. Conversely, if the filler 120 is well dispersed, the matrix 110 may be sufficiently filled in the spaces between the fillers while the matrix 110 and the filler 120 are sufficiently mixed, thereby reducing voids.
[0053] As the voids in the film 100 decrease, the tensile strength, Young's modulus, elongation, indentation hardness, and light transmittance of the film 100 increase and the yellowness and haze decrease, resulting in excellent mechanical properties such as abrasion resistance and flexibility, and excellent optical properties such as light transmittance and visibility.
[0054] According to one embodiment of the present invention, the true density ratio (DR) of film 100 to density gradient tube density is less than or equal to 1.10.
[0055] If the true density ratio (DR) to the density gradient tube density exceeds 1.10, the filling effect of the filler 120 in the film 100 decreases, and the effect of improving the hardness and Young's modulus of the film 100 decreases. In addition, an increase in voids in the film 100 caused by the aggregation of the filler 120 causes a problem that the elongation rate and indentation hardness of the film 100 decrease. In addition, the haze of the film 100 increases due to the aggregation of the filler 120.
[0056] In the polyimide-based film 100 according to one embodiment of the present invention, the particle volume concentration (PVC) of the film 100 is 5 to 38%.
[0057] The particle volume concentration (PVC) of the film 100 is calculated by Equation 2 below.
[0058] <Expression 2> PVC(%)=[V1 / (V1+V2)]*100
[0059] In Equation 2, V1 is the volume of the filler and V2 is the volume of the matrix.
[0060] Hereinafter, the particle volume concentration (PVC) will be specifically described with reference to Fig. 3. Fig. 3 shows the difference in voids inside the film 100 depending on the particle volume concentration (PVC) of the film 100.
[0061] The particle volume concentration (PVC) is the percentage (%) of the volume that the filler 120 occupies relative to the total volume of the matrix 110 and the filler 120 in the film 100 .
[0062] As shown in FIG. 3, when the particle volume concentration (PVC) of the film 100 decreases, the voids of the film 100 decrease, and when the particle volume concentration (PVC) increases, the voids of the film 100 increase.
[0063] As the particle volume concentration (PVC) of the film 100 increases, the volume occupied by the fillers 120 in the film 100 increases and the average distance between the fillers decreases. As the average distance between the fillers decreases, the matrix 110 is less able to fill the spaces between the fillers, and voids increase.
[0064] The volume (V1) of the filler can be calculated by dividing the mass of the filler by the density. Specifically, the mass and density of the filler contained in the film 100 can be measured to calculate the volume (V1) of the filler. For example, the mass of the filler can be determined by measuring the weight of the filler added when manufacturing the film 100. The density of the filler can be measured using the true density measurement method or density gradient tube density measurement method described above.
[0065] The volume (V2) of the matrix can be calculated by dividing the mass of the matrix by the density. Specifically, the mass and density of the matrix contained in the film 100 can be measured to calculate the volume (V2) of the matrix. For example, the mass of the matrix can be determined by measuring the weight of the matrix added when manufacturing the film 100. The density of the matrix can be measured using the true density measurement method or density gradient tube density measurement method described above.
[0066] According to one embodiment of the present invention, the particle volume concentration (PVC) of the film 100 is between 5 and 38%.
[0067] If the particle volume concentration (PVC) is less than 5%, the filler 120 has little effect on improving the mechanical properties of the film 100. If the particle volume concentration (PVC) exceeds 38%, discontinuity occurs at the contact surface between the filler 120 and the matrix 110, resulting in a decrease in elongation and indentation hardness.
[0068] According to an embodiment of the present invention, the polyimide matrix 110 has optical transparency and flexibility, e.g., bending, folding and rollable properties.
[0069] The polyimide-based matrix 110 includes a polyimide-based resin. The polyimide-based matrix 110 can be made of, for example, a polyimide-based resin.
[0070] The polyimide-based matrix 110 according to an embodiment of the present invention may be prepared from monomer components including a dianhydride and a diamine.
[0071] More specifically, the polyimide-based matrix 110 according to one embodiment of the present invention has imide repeat units formed by a dianhydride and a diamine.
[0072] However, the polyimide-based matrix 110 according to an embodiment of the present invention is not limited thereto. The polyimide-based matrix 110 according to an embodiment of the present invention may be manufactured from monomer components further including a dicarbonyl compound in addition to a dianhydride and a diamine. Therefore, the polyimide-based matrix 110 according to an embodiment of the present invention may have imide repeat units and amide repeat units. An example of the polyimide-based matrix 110 having imide repeat units and amide repeat units is a polyamide-imide resin.
[0073] Therefore, the polyimide-based matrix 110 according to an embodiment of the present invention may include a polyimide resin or a polyamide-imide resin.
[0074] According to an embodiment of the present invention, the polyimide resin used as the polyimide matrix 110 may have excellent mechanical and optical properties.
[0075] The polyimide matrix 110 may have a thickness sufficient for the polyimide film 100 to protect the display panel. For example, the polyimide matrix 110 may have a thickness of 10 to 100 μm.
[0076] The polyimide matrix 110 may have an average light transmittance of 85% or more in the visible light region and a yellowness index of 5 or less when measured with a UV spectrophotometer, based on a thickness of 10 to 100 μm.
[0077] According to an embodiment of the present invention, the filler 120 may be inorganic or organic. The filler 120 may have a particle shape. According to an embodiment of the present invention, an inorganic filler may be used.
[0078] According to an embodiment of the present invention, the filler 120 may include at least one of silica (SiO2), zirconia (ZrO2), alumina (Al2O3), titanium dioxide (TiO2), styrene, and acrylic. For example, silica (SiO2) particles, which are inorganic, may be used as the filler 120.
[0079] According to an embodiment of the present invention, at least a portion of the silica (SiO2) used as the filler 120 may be surface-treated. More specifically, surface-treated silica (SiO2) particles may be used as the filler 120.
[0080] According to an embodiment of the present invention, at least a portion of the silica (SiO2) used as the filler 120 may be surface-treated with an organic compound having an alkoxy group. For example, silica (SiO2) particles surface-treated with at least one of substituted or unsubstituted alkylalkoxysilane and phenylalkoxysilane may be used as the filler 120.
[0081] Specifically, silica (SiO2) particles that have been surface-treated with methylalkoxysilane, ethylalkoxysilane, or phenylalkoxysilane can be used as the filler 120. More specifically, silica (SiO2) particles that have been surface-treated with trimethoxy(methyl)silane or phenyltrimethoxysilane can be used as the filler 120.
[0082] According to an embodiment of the present invention, the filler 120 may have unit structures represented by the following Chemical Formulas 1 to 7.
[0083] [ka]
[0084] [ka]
[0085] [ka]
[0086] [ka]
[0087] [ka]
[0088] [ka]
[0089] In Chemical Formula 1 to Chemical Formula 6, each R can independently be at least one of an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and a phenyl group having 6 to 18 carbon atoms.
[0090] The polyimide-based film 100 according to an embodiment of the present invention has excellent mechanical and optical properties.
[0091] Regarding optical properties, the polyimide-based film 100 according to an embodiment of the present invention may have a yellowness index of 3 or less. In addition, the polyimide-based film 100 according to an embodiment of the present invention may have a haze of 1% or less. The polyimide-based film 100 according to an embodiment of the present invention may have a light transmittance of 85% or more.
[0092] Furthermore, with regard to mechanical properties, the polyimide-based film 100 according to an embodiment of the present invention may have a Young's modulus of 5.0 GPa or more. Also, the polyimide-based film 100 according to an embodiment of the present invention may have an elongation rate of 15% or more. Also, the polyimide-based film 100 according to an embodiment of the present invention may have an indentation hardness of 45 or more.
[0093] According to one embodiment of the present invention, the particle size of the filler 120, the content of the filler 120, and the particle spacing can be adjusted so that the polyimide-based film 100 has excellent optical and mechanical properties.
[0094] In addition, in order to uniformly mix the filler 120 into the polyimide-based matrix 110 so that the polyimide-based film 100 has excellent optical and mechanical properties, one embodiment of the present invention provides a new method for mixing the polyimide-based polymer constituting the polyimide base matrix 110 with the filler 120.
[0095] According to an embodiment of the present invention, the filler 120 may have an average particle size of 5 to 50 nm. If the average particle size of the filler 120 is less than 5 nm, the dispersibility of the filler 120 may decrease, and the filler 120 may aggregate. On the other hand, if the average particle size of the filler 120 exceeds 50 nm, the optical properties of the polyimide-based film 100 including the filler 120 may decrease. For example, if an excessive amount of the filler 120 having an average particle size exceeding 50 nm is included, the haze of the polyimide-based film 100 may increase.
[0096] Furthermore, if the average particle size of the filler 120 is less than 5 nm, the filler 120 may aggregate, reducing the mechanical strength of the polyimide film 100 in the area where the filler 120 aggregates, thereby reducing the tensile strength, Young's modulus, and compression hardness of the polyimide film 100. If the average particle size of the filler 120 exceeds 50 nm, the elongation of the polyimide film 100 may be less than 15%.
[0097] Furthermore, if the average particle size of the filler 120 is less than 5 nm, the dispersibility of the filler 120 may decrease, and if the average particle size of the filler 120 exceeds 50 nm, the spacing between the filler 120 may not be sufficiently secured. Therefore, the true density ratio (DR) to the density gradient tube density may exceed 1.10.
[0098] According to another embodiment of the present invention, the filler 120 may have an average particle size of 10 to 20 nm, or may have an average particle size of 10 to 15 nm.
[0099] When the polyimide film 100 contains the filler 120 having a particle size in nanometers, the optical properties of the polyimide film 100 can be improved due to light scattering by the filler 120. Furthermore, when the polyimide film 100 contains the filler 120, the mechanical properties of the polyimide film 100 can be improved.
[0100] According to an embodiment of the present invention, the content of the filler 120 may be in the range of 5 to 50% by weight based on the total weight of the polyimide-based film 100 .
[0101] If the content of the filler 120 is less than 5% by weight based on the total weight of the polyimide-based film 100, the light scattering effect of the filler 120 may be slight, and the effect of improving the light transmittance of the polyimide-based film 100 may be almost nonexistent. Also, if the content of the filler 120 is less than 5% by weight based on the total weight of the polyimide-based film 100, the effect of improving the tensile strength, Young's modulus, elongation, and hardness of the polyimide-based film 100 may be slight.
[0102] On the other hand, if the content of the filler 120 exceeds 50 weight % based on the total weight of the polyimide-based film 100, the dispersibility of the filler 120 decreases, the haze of the polyimide-based film 100 decreases, and the excess filler 120 may block light, reducing the light transmittance of the polyimide-based film 100.
[0103] FIG. 4 is a schematic diagram illustrating the dispersion state of the filler 120 in the polyimide film 100 according to one embodiment of the present invention.
[0104] As shown in Fig. 4, some of the fillers 120 are dispersed and spaced apart from one another, while some form aggregates. In Fig. 4, "Group A" indicates fillers 120 that form aggregates. Fillers 120 other than "Group A" fillers 120 indicate fillers 120 that are dispersed without agglomeration (portions other than Group A). The fewer the number of fillers 120 that form aggregates such as "Group A" in Fig. 4, the more uniformly the fillers 120 are dispersed within the polyimide-based film 100.
[0105] 4, when the amount of filler 120 forming aggregates such as "Group A" is small, the true density ratio (DR) to the density gradient tube density is 1.10 or less, and the polyimide-based film 100 can have excellent tensile strength, Young's modulus, elongation, and indentation hardness. Also, when the amount of filler 120 forming aggregates such as "Group A" is small, the particle volume concentration (PVC) is in the range of 5 to 38%, and the polyimide-based film 100 can have excellent tensile strength and Young's modulus.
[0106] In general, if the filler 120 is included and is not sufficiently uniformly dispersed, the polyimide film 100 may have reduced tensile strength, Young's modulus, elongation, indentation hardness, and light transmittance, and increased yellowness and haze, resulting in reduced mechanical and optical properties. However, according to an embodiment of the present invention, the ratio of true density (DR) to density gradient tube density is set to 1.10 or less, thereby preventing the polyimide film 100 from having reduced tensile strength, Young's modulus, elongation, indentation hardness, and light transmittance, and from having increased yellowness and haze.
[0107] Furthermore, according to one embodiment of the present invention, by setting the particle volume concentration (PVC) to 5 to 38%, it is possible to prevent the tensile strength and Young's modulus of the polyimide film 100 from decreasing.
[0108] According to an embodiment of the present invention, the true density ratio (DR) of the polyimide-based film 100 to the density gradient tube density is 1.10 or less, and the polyimide-based film 100 can have a Young's modulus of 5.0 GPa or more.
[0109] Furthermore, according to an embodiment of the present invention, the polyimide film 100 may have an elongation rate of 15% or more.
[0110] Furthermore, according to an embodiment of the present invention, the polyimide-based film 100 may have an indentation hardness of 45 or more.
[0111] Furthermore, according to an embodiment of the present invention, the polyimide film 100 may have a light transmittance of 85% or more.
[0112] Furthermore, according to an embodiment of the present invention, the polyimide film 100 may have a haze of 1% or less.
[0113] Furthermore, according to one embodiment of the present invention, the polyimide-based film 100 may have a yellowness index of 3.0 or less.
[0114] FIG. 5 is a cross-sectional view of a portion of a display device 200 according to another embodiment of the present invention, and FIG. 6 is an enlarged cross-sectional view of a portion "P" in FIG.
[0115] Referring to FIG. 5, a display device 200 according to another embodiment of the present invention includes a display panel 501 and a polyimide-based film 100 on the display panel 501 .
[0116] 5 and 6, a display panel 501 includes a substrate 510, a thin film transistor (TFT) on the substrate 510, and an organic light emitting element 570 connected to the thin film transistor (TFT). The organic light emitting element 570 includes a first electrode 571, an organic light emitting layer 572 on the first electrode 571, and a second electrode 573 on the organic light emitting layer 572. The display device 200 disclosed in FIGS. 5 and 6 is an organic light emitting display device.
[0117] The substrate 510 may be made of glass or plastic. Specifically, the substrate 510 may be made of plastic such as polyimide resin or polyimide film. Although not shown, a buffer layer may be disposed on the substrate 510.
[0118] The thin film transistor (TFT) is disposed on a substrate 510. The thin film transistor (TFT) includes a semiconductor layer 520, a gate electrode 530 insulated from the semiconductor layer 520 and overlapping at least a portion of the semiconductor layer 520, a source electrode 541 connected to the semiconductor layer 520, and a drain electrode 542 spaced apart from the source electrode 541 and connected to the semiconductor layer 520.
[0119] 6, a gate insulating film 535 is disposed between a gate electrode 530 and a semiconductor layer 520. An interlayer insulating film 551 may be disposed on the gate electrode 530, and a source electrode 541 and a source electrode 542 may be disposed on the interlayer insulating film 551.
[0120] The planarization film 552 is disposed on the thin film transistor TFT to planarize the upper portion of the thin film transistor TFT.
[0121] The first electrode 571 is disposed on the planarization film 552. The first electrode 571 is connected to a thin film transistor (TFT) via a contact hole provided in the planarization film 552.
[0122] The bank layer 580 is disposed on a part of the first electrode 571 and the planarization film 552 to define a pixel region or a light-emitting region. For example, the bank layer 580 can be disposed in a matrix structure in a boundary region between a plurality of pixels to define a pixel region by the bank layer 580.
[0123] The organic light-emitting layer 572 is disposed on the first electrode 571. The organic light-emitting layer 572 may also be disposed on the bank layer 580. The organic light-emitting layer 572 may include one light-emitting layer, or may include two light-emitting layers stacked one above the other. The organic light-emitting layer 572 may emit light having any one of red, green, and blue colors, and may emit white light.
[0124] A second electrode 573 is disposed on the organic light-emitting layer 572 .
[0125] The first electrode 571, the organic light emitting layer 572, and the second electrode 573 may be stacked to form the organic light emitting element 270.
[0126] Although not shown, when the organic light emitting layer 572 emits white light, each pixel may include a color filter for filtering the white light emitted from the organic light emitting layer 572 by wavelength. The color filter is formed on the path of light travel.
[0127] A thin film encapsulation layer 590 may be disposed on the second electrode 573. The thin film encapsulation layer 590 may include at least one organic film and at least one inorganic film, and the at least one organic film and the at least one inorganic film may be alternately disposed.
[0128] A polyimide-based film 100 is disposed on a display panel 501 having the above-mentioned laminated structure. The polyimide-based film 100 includes a polyimide-based matrix 110 and a filler 120 dispersed in the polyimide-based matrix 110.
[0129] The polyimide-based film 100 according to an embodiment of the present invention can be manufactured by a hybrid blending method in which solution-to-solution blending and solution-to-powder blending are performed in parallel.
[0130] According to one embodiment of the present invention, a method for producing a polyimide-based film 100 includes the steps of preparing a polyimide-based resin powder, dissolving a first content of the polyimide-based resin powder in a first solvent to prepare a polyimide-based resin solution, dispersing a filler in a second solvent to prepare a filler dispersion, mixing the filler dispersion and the polyimide-based resin solution to prepare a first mixed liquid, and adding and dissolving a second content of the polyimide-based resin powder in the first mixed liquid to prepare a second mixed liquid.
[0131] According to one embodiment of the present invention, the polyimide resin powder is mixed with the filler dispersion in at least two portions.
[0132] Specifically, the first content in the polyimide-based resin powder is dissolved in a first solvent and mixed with the filler dispersion in the form of a polyimide-based resin solution. The first content may be 0.5 to 10% by weight of the filler, and preferably 1 to 5%.
[0133] The second content in the polyimide-based resin powder is added in a powder state. Specifically, the second content in the polyimide-based resin powder can be added in a powder state to a first mixed liquid obtained by mixing a filler dispersion and a polyimide-based resin solution.
[0134] The second content of the polyimide-based resin powder can be 10 to 200 times the first content. More specifically, the second content of the polyimide-based resin powder can be 60 to 200 times the first content.
[0135] According to an embodiment of the present invention, the method may further include adding a third solvent to the first mixed solution before adding the second content of the polyimide-based resin powder to the first mixed solution. The third solvent may be the same as or different from the first solvent. According to an embodiment of the present invention, the third solvent may be the same as the first solvent.
[0136] The first solvent may be DMAc (N,N-Dimethylacetamide). The second solvent may be DMAc (N,N-Dimethylacetamide) or MEK (Methyl Ethyl Ketone). The third solvent may be DMAc (N,N-Dimethylacetamide). However, an embodiment of the present invention is not limited thereto, and other known solvents may be used as the first solvent, the second solvent, and the third solvent.
[0137] According to one embodiment of the present invention, first, a part (first content) of the polyimide resin powder is dissolved in a solvent and then mixed with the filler dispersion liquid, thereby improving the dispersibility of the filler.
[0138] For reference, when a polyimide-based resin powder is directly added to a filler dispersion liquid in which a filler is dispersed, the solvent instantaneously penetrates into the inside of the powder from the surface of the powder, and at this time, the concentration around the powder surface instantaneously increases, which may cause the filler to aggregate.
[0139] Meanwhile, according to one embodiment of the present invention, by first adding a polyimide resin that has already been dissolved to a filler dispersion liquid containing a solvent, the polymer chains of the polyimide resin distributed among the fillers can prevent the aggregation of the fillers. Even if polyimide resin powder is then added again (second content addition), no aggregation occurs between the fillers. This prevents the aggregation of the fillers and improves the dispersibility of the fillers.
[0140] According to an embodiment of the present invention, a polyimide-based film 100 containing a uniformly dispersed filler can be manufactured by a hybrid mixing method in which solution-to-solution mixing and solution-to-powder mixing are performed in parallel.
[0141] According to an embodiment of the present invention, a high degree of freedom between the filler 120 and the polyimide resin can be maintained, creating an environment that facilitates dispersion. As a result, the filler 120 and the polyimide resin can be bonded in a high degree of freedom state, and the polyimide film 100 in which the filler 120 is uniformly dispersed in the matrix 110 formed by the polyimide resin can be manufactured.
[0142] According to one embodiment of the present invention, silica particles can be used as the filler 120. The silica particles can be made from, for example, tetraethyltriethoxysilane.
[0143] Specifically, ethanol and tetraethyltriethoxysilane (TEOS, Si(OC2H5)4) are added to a reactor and stirred at room temperature, and NH4OH is added to this, and the reaction product obtained by stirring is filtered, washed with ethanol, and then dried under reduced pressure to produce silica particles [SiO2] with an average particle size of approximately 20 nm.
[0144] A silica dispersion can be used as the dispersion of the filler 120. The silica dispersion can be produced, for example, by adding DMAc (Dimethylacetamide) and silica particles to a reactor and stirring them.
[0145] The present invention will be described in more detail below with reference to illustrative manufacturing examples and examples. However, the present invention is not limited to the manufacturing examples and examples described below.
[0146] <Production Example 1: Production of polyimide-based polymer solid> A 1L reactor equipped with a stirrer, nitrogen injector, dropping funnel, temperature controller and cooler was filled with 776.655g of DMAc (N,N-Dimethylacetamide) while passing nitrogen through it, and the temperature of the reactor was set to 25°C, and 54.439g (0.17 mol) of TFDB was dissolved, and the solution was maintained at 25°C. 15.005g (0.051 mol) of BPDA was added to the solution, and the mixture was stirred for 3 hours to completely dissolve BPDA, and then 22.657g (0.051 mol) of 6FDA was added and completely dissolved. The temperature of the reactor was lowered to 10°C, and 13.805g (0.068 mol) of TPC was added, and the mixture was reacted at 25°C for 12 hours to obtain a polymer solution with a solid concentration of 12% by weight.
[0147] 17.75g of pyridine and 22.92g of acetyl anhydride were added to the obtained polymer solution and stirred for 30 minutes, then stirred again at 70°C for 1 hour and cooled to room temperature, 20L of methanol was added to the obtained polymer solution to precipitate a solid, the precipitated solid was filtered and pulverized, washed again with 2L of methanol, and dried at 100°C in vacuum for 6 hours to obtain a powdered polyimide-based polymer solid. The polyimide-based polymer solid produced here was a polyamide-imide polymer solid.
[0148] <Example 1> A 1 L reactor was filled with 35.42 parts by weight of DMAc (first solvent), and the contents were stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.36 parts by weight (first content) of the solid powder polyamide-imide (polyimide resin powder) produced in Preparation Example 1 was added, and the mixture was stirred for 1 hour and then heated to 25° C. to produce a liquid polyimide resin solution.
[0149] Another 1 L reactor was charged with 23.85 parts by weight of silica dispersion A (SSD_330T, Ranco) in which silica particles having an average particle size of 10 nm were dispersed at a content of 30 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the reactor temperature was kept at 25° C., and the liquid polyimide-based resin solution prepared above was slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the polyimide-based resin solution were mixed.
[0150] 348.23 parts by weight of DMAc as a third solvent was added to the first mixed solution and stirred, and 64.04 parts by weight (second content) of the solid powder polyamide-imide (polyimide resin powder) produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a polyimide resin solution in which silica particles are dispersed.
[0151] The obtained second mixture liquid was cast. A casting substrate is used for casting. There is no particular limitation on the type of the casting substrate. The casting substrate may be a glass substrate, a stainless steel (SUS) substrate, a Teflon substrate, or the like. According to an embodiment of the present invention, an organic substrate may be used as the casting substrate.
[0152] Specifically, the obtained second mixed liquid was applied and cast onto a glass substrate, and then dried with hot air at 120°C for 30 minutes to produce a film. The produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0153] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a polyimide film. The polyimide film was again heat-treated at 250°C for 5 minutes.
[0154] As a result, a polyimide-based film 100 having a thickness of 50 μm was completed, which contained a polyimide-based matrix 110 and silica-based filler 120 dispersed in the polyimide-based matrix.
[0155] <Examples 2 to 7> Polyimide-based films of Examples 2 to 7 were produced in the same manner as in Example 1, with only the silica dispersion, the content of the silica dispersion, the first content, the second content, the content of the first solvent, and the content of the third solvent being different.
[0156] The specific silica dispersions, the contents of the silica dispersions, the first contents, the second contents, the first solvent contents, and the third solvent contents of Examples 1 to 7 are as shown in Table 1 below.
[0157] <Comparative Example 1> Polyimide films 100 were produced in the same manner as in Example 1, except that the silica dispersion, the content of the silica dispersion, the first content, the second content, the content of the first solvent, and the content of the third solvent were varied.
[0158] The specific silica dispersion, the content of the silica dispersion, the first content, the second content, the content of the first solvent, and the content of the third solvent in Comparative Example 1 are as shown in Table 1 below.
[0159] <Comparative Example 2> A 1L reactor was filled with 35.80 parts by weight of silica dispersion C (50nmSP-AD1, Admatechs) in which silica particles with an average particle size of 50nm were dispersed at a content of 20% by weight in a DMAc (N,N-dimethylacetamide) solution (second solvent), and then 371.73 parts by weight of DMAc (third solvent) was added and stirred. 64.40 parts by weight (second content) of the solid powder polyamide-imide (polyimide resin powder) produced in Preparation Example 1 was added to the stirred solution and stirred to produce a mixture in which the silica dispersion and polyimide resin were mixed. The mixture is a polyimide resin solution in which silica particles are dispersed.
[0160] The resulting mixture was cast. The casting and subsequent steps were the same as in Example 1 to produce a polyimide film 100.
[0161] <Comparative Example 3> A 1L reactor was filled with 35.80 parts by weight of silica dispersion D (DMAc-ST-ZL, Nissan) in which silica particles with an average particle size of 70 nm were dispersed at a content of 20% by weight in a DMAc (N,N-dimethylacetamide) solution (second solvent), and then 371.06 parts by weight of DMAc (third solvent) was added and stirred. 64.40 parts by weight (second content) of the solid powder polyamide-imide (polyimide resin powder) produced in Preparation Example 1 was added to the stirred solution and stirred to produce a mixture in which the silica dispersion and polyimide resin were mixed. The mixture is a polyimide resin solution in which silica particles are dispersed.
[0162] The resulting mixture was cast. The casting and subsequent steps were the same as in Example 1 to produce a polyimide film 100.
[0163] <Comparative Examples 4 to 7> Polyimide-based films 100 of Comparative Examples 4 to 7 were produced in the same manner as in Example 1, except that the silica dispersion, the content of the silica dispersion, the first content, the second content, the content of the first solvent, and the content of the third solvent were varied.
[0164] Specific silica dispersions, the contents of the silica dispersions, the first contents, the second contents, the first solvent contents, and the third solvent contents of Comparative Examples 4 to 7 are as shown in Table 1 below.
[0165] [Table 1] TIFF0007617241000008.tif163170
[0166] <Measurement example> The polyimide films produced in Examples 1 to 7 and Comparative Examples 1 to 7 were subjected to the following measurements.
[0167] 1) Measurement of true density ratio (DR) to density gradient tube density The true density and density gradient tube density of the polyimide-based film were measured as follows, and the true density ratio (DR) of the polyimide-based film to the density gradient tube density was calculated according to the following Equation 1.
[0168] <Expression 1> DR = true density / density gradient tube density
[0169] (1) Measurement of true density Polyimide film 100 sample (10 x 10 cm 2 ) 1×1cm 2 The specimen was cut into small pieces of the following size and placed in a sample holder together with iron balls (crushed material). A cryo-crusher (Japan Analytical Industry, JFC-300) was filled with more than 2 / 3 liquid nitrogen, and the sample holder containing the cut specimen was connected to the cryo-crusher. The chamber was then closed and the specimen was crushed using the cryo-crusher at a pre-cool rate of 15 minutes / run for more than 15 minutes. The true density of the crushed film 100 sample was measured seven times using a Micromeritics AccuPyc 1340 Pycnometer (using helium gas). The highest and lowest true density values of the measured film 100 were excluded, and the remaining true density values were averaged to calculate the true density of the polyimide film 100.
[0170] (2) Measurement of density gradient tube density The density gradient tube density of the polyimide-based film 100 was measured using a density gradient tube according to standard ASTM D1505.
[0171] 2) Measurement of particle volume concentration (PVC) The volume (V1) of the filler and the volume (V2) of the matrix of the polyimide-based film were measured, and then the particle volume concentration (PVC) of the polyimide-based film was calculated according to the following formula 2.
[0172] <Expression 2> PVC(%)=[V1 / (V1+V2)]*100
[0173] In Equation 2, V1 is the volume of the filler and V2 is the volume of the matrix.
[0174] The volume (V1) of the filler can be calculated by dividing the mass of the filler by the density. Specifically, the mass and density of the filler contained in the film 100 can be measured to calculate the volume (V1) of the filler. For example, the mass of the filler can be determined by measuring the weight of the filler added when manufacturing the film 100. The density of the filler can be measured using the true density measurement method or density gradient tube density measurement method described above.
[0175] The volume (V2) of the matrix can be calculated by dividing the mass of the matrix by the density. Specifically, the mass and density of the matrix contained in the film 100 can be measured to calculate the volume (V2) of the matrix. For example, the mass of the matrix can be determined by measuring the weight of the matrix added when manufacturing the film 100. The density of the matrix can be measured using the true density measurement method or density gradient tube density measurement method described above.
[0176] 3) Young's modulus and elongation: Young's modulus and elongation of the polyimide film were measured using an Instron universal tensile tester according to ASTM D885.
[0177] 4) Indentation hardness: The prepared polyimide film was cut into 2cm x 10cm pieces and the HV value was measured using a Fischerscope HM2000 (HELMUT FISCHER) (measurement conditions: F=12,000mN / 12s, C=5.0s). The measurement was carried out a total of 7 times, and the highest and lowest values were excluded, and the remaining HV values were averaged to calculate the indentation hardness of the polyimide film.
[0178] 5) Light transmittance (%): The average optical transmittance was measured at wavelengths of 360 to 740 nm using a Spectrophotometer (CM-3700D, KONICA MINOLTA) according to standard ASTM E313.
[0179] 6) Yellowness: Yellowness was measured using a Spectrophotometer (CM-3700D, KONICA MINOLTA) according to standard ASTM E313.
[0180] 7) Haze: The produced polyimide film was cut into a piece of 50 mm x 50 mm, and measured five times according to ASTM D1003 using a Murakami haze meter (model: HM-150), and the average value was used as the haze value.
[0181] The measurement results are shown in Tables 2 and 3 below.
[0182] [Table 2]
[0183] [Table 3]
[0184] As shown in the measurement results in Tables 2 and 3, the polyimide film 100 according to the embodiment of the present invention has a true density ratio (DR) to density gradient tube density of 1.10 or less, and is excellent in mechanical properties such as Young's modulus, elongation, and indentation hardness, and is also excellent in optical properties such as excellent light transmittance, low yellowness, and low haze. However, in Comparative Example 1, the filler content is more than 50 wt% with respect to the total weight of the polyimide film, and the true density ratio (DR) to density gradient tube density is more than 1.10, the particle volume concentration (PVC) is more than 38%, and the Young's modulus of the polyimide film is less than 5.0 GPa, the elongation is less than 15%, the indentation hardness is less than 45%, and the yellowness is more than 3.0. In Comparative Example 2, the polyimide resin powder was mixed with the filler dispersion liquid without distinguishing between the first and second contents, and the true density ratio (DR) to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, and the yellowness index exceeded 3.0.
[0185] In Comparative Example 3, the polyimide resin powder was mixed with the filler dispersion liquid without being divided into the first and second contents, and further, the average particle size of the filler exceeded 50 nm, the true density ratio (DR) to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, the yellowness index exceeded 3.0, and the haze exceeded 1%.
[0186] In Comparative Example 4, the average particle size of the filler exceeded 50 nm, the true density ratio (DR) to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, the yellowness index exceeded 3.0, and the haze exceeded 1%.
[0187] In Comparative Example 5, the first content of the polyimide-based resin powder relative to the filler weight was less than 0.5%, the true density ratio (DR) relative to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide-based film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, and the yellowness index exceeded 3.0.
[0188] In Comparative Example 6, the first content of the polyimide-based resin powder relative to the filler weight exceeded 10%, the true density ratio (DR) relative to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide-based film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, and the yellowness index exceeded 3.0.
[0189] In Comparative Example 7, the filler content was less than 5 wt % relative to the total weight of the polyimide film, the true density ratio (DR) to the density gradient tube density exceeded 1.10, and the Young's modulus of the polyimide film was less than 5.0 GPa, the elongation was less than 15%, the indentation hardness was less than 45%, and the yellowness index exceeded 3.0. [Explanation of symbols]
[0190] 100: Polyimide film 110: Polyimide matrix 120: Filler 200:Display device 501: Display panel
Claims
1. A polyimide matrix; and a filler dispersed in the polyimide matrix, A true density ratio (DR) to density gradient tube density of 1.10 or less; The average particle size of the filler is 5 to 50 nm; A polyimide-based film, the filler content being 5 to 50% by weight based on the total weight of the film. The true density ratio (DR) to the density gradient tube density is calculated by the following formula 1. <Formula 1> Density Ratio (DR) = true density / density gradient tube density
2. 2. The polyimide-based film according to claim 1, characterized in that it has a particle volume concentration (PVC) of 5 to 38%: The particle volume concentration (PVC) is calculated by the following formula 2. <Formula 2> PVC (%) = [V] 1 / (V 1 +V 2 )]*100 In the above formula 2, V 1 is the volume of the filler, V 2 is the volume of the matrix.
3. The filler is silica (SiO 2 2. The polyimide film according to claim 1, further comprising:
4. The silica (SiO 2 4. The polyimide film according to claim 3, wherein at least a part of said first and second polymers is surface-treated with an organic compound having an alkoxy group.
5. 2. The polyimide film according to claim 1, which has a Young's modulus of 5.0 GPa or more.
6. 2. The polyimide film according to claim 1, which has an elongation of 15% or more.
7. 2. The polyimide film according to claim 1, which has an indentation hardness of 45 or more.
8. 2. The polyimide film according to claim 1, which has a yellowness index of 3 or less.
9. 2. The polyimide film according to claim 1, which has a haze of 1% or less.
10. 2. The polyimide film according to claim 1, which has a light transmittance of 85% or more.
11. A display panel; The polyimide-based film according to any one of claims 1 to 10, which is disposed on the display panel; A display device comprising:
Citation Information
Patent Citations
Polyimide product having medium electrical conductivity and preparation thereof
JP1990110138A
Polyimide film
JP2005306940A
Apparatus for manufacturing polyimide film
JP2006327022A
Surface-modified composite silica particles and polyimide film containing the same
JP2017520662A
Optical film
JP2019194327A